Deteksi Bakteri Gram-Negatif Pada Permukaan Daun Kemangi (Ocimum basilicum) dari Tiga Pasar Tradisional di Bogor: Detection of Gram-Negative Bacteria on the Leaf Surface of Basil (Ocimum basilicum) Collected from Three Traditional Markets in Bogor - Getriani, Zerina; Priyanto, Jepri Agung; Budiarti, Sri (Jurnal Sumberdaya Hayati, 2023)
Ocimum basilicum or basil is commonly consumed raw by Indonesian. However, it is easily contaminated by pathogenic bacteria. This study aimed to detect Gram-negative bacteria in basil leaves obtained from three traditional markets in Bogor. Isolation and quantification of bacteria using serial dilution showed that the average number of bacteria on the surface of basil leaves was 9.6 × 107 CFU/g. Basil leaves obtained from the second traditional market had the highest number of bacteria of 11.3 × 107 CFU/g. All isolated bacteria have the same morphology namely bacilli, then further purified and characterized physiologically. The nine bacterial isolates obtained were able to grow on the selective-differential media including Salmonella-Shigella agar (SSA), bismuth sulphite agar (BSA), and eosin-methylen blue (EMBA). Gram staining showed that all bacterial isolates were classified as Gram-negative bacteria. The hemolytic ability of bacterial isolates was tested using blood agar base media, three out of nine bacterial isolates were able to produce hemolysin. Molecular identification based on 16S rRNA sequences showed that the bacterial isolates belonged to the Providencia sp., Proteus sp., Pseudomonas sp., and Kluyvera sp.